L‐Dopa responsiveness is associated with distinctive connectivity patterns in advanced Parkinson's disease. Issue 6 (8th May 2017) - Akram, Harith; Wu, Chengyuan; Hyam, Jonathan; Foltynie, Thomas; Limousin, Patricia; De Vita, Enrico; Yousry, Tarek; Jahanshahi, Marjan; Hariz, Marwan; Behrens, Timothy; Ashburner, John; Zrinzo, Ludvic
ABSTRACT: Background : Neuronal loss and dopamine depletion alter motor signal processing between cortical motor areas, basal ganglia, and the thalamus, resulting in the motor manifestations of Parkinson's disease. Dopamine replacement therapy can reverse these manifestations with varying degrees of improvement. Methods : To evaluate functional connectivity in patients with advanced Parkinson's disease and changes in functional connectivity in relation to the degree of response tol ‐dopa, 19 patients with advanced Parkinson's disease underwent resting‐state functional magnetic resonance imaging in the on‐medication state. Scans were obtained on a 3‐Tesla scanner in 3 × 3 × 2.5 mm 3 voxels. Seed‐based bivariate regression analyses were carried out with atlas‐defined basal ganglia regions as seeds, to explore relationships between functional connectivity and improvement in the motor section of the UPDRS‐III following anl ‐dopa challenge. False discovery rate‐corrected P was set at < 0.05 for a 2‐tailed t test. Results : A greater improvement in UPDRS‐III scores followingl ‐dopa administration was characterized by higher resting‐state functional connectivity between the prefrontal cortex and the striatum ( P = 0.001) and lower resting‐state functional connectivity between the pallidum ( P = 0.001), subthalamic nucleus ( P = 0.003), and the paracentral lobule (supplementary motor area, mesial primary motor, and primary sensory areas). Conclusions : Our findings show characteristic basal ganglia resting‐state functional connectivity patterns associated with different degrees ofl‐ dopa responsiveness in patients with advanced Parkinson's disease.l‐ Dopa exerts a graduated influence on remapping connectivity in distinct motor control networks, potentially explaining some of the variance in treatment response. © 2017 International Parkinson and Movement Disorder Society